Lower achievement of guideline recommended care in Canadian adults with early-onset diabetes: A population-based cohort study - Sriskandarajah, Apishanthi; Metcalfe, Amy; Nerenberg, Kara A.; Butalia, Sonia (Diabetes research and clinical practice, 2024)
•It’s unclear why early-onset diabetes is associated with an increased risk of complications.•Those with early-onset diabetes had lower frequency of HbA1c testing and sub-optimal control.•Those with early-onset diabetes had lower concordance with guideline recommended care.•Strategies to improve diabetes management in those with early-onset diabetes are needed. Adults with early-onset diabetes (age < 40 years) have an increased risk of complications, and it is unclear whether they are receiving guideline recommended care. We compared the frequency and results of haemoglobin A1c (HbA1c) testing in adults with early-onset and usual-onset diabetes and assessed factors related to guideline concordance. Population-level databases from Alberta, Canada (∼4.5 million) were used to identify adults with incident diabetes. The cohort was stratified by age at diagnosis (< 40 vs. ≥ 40 years) and then followed for 365 days for HbA1c testing. Adjusted multivariable analyses were used to identify clinical and sociodemographic factors associated with guideline concordance. Among 23,643 adults with incident diabetes (mean age 54.1 ± 15.4 years; 42.1 % female), 18.9 % had early-onset diabetes. Early-onset diabetes was associated with lower frequency of testing (adjusted odds ratio (aOR), 0.80; 95 % CI 0.70–0.90) and above target glycaemic levels compared to usual-onset diabetes (aOR, 1.45; 95 % CI 1.29–1.64). Factors associated with guideline concordant frequency of HbA1c testing were rural residence and insulin use. In our universal care setting with premium-free health care, early-onset diabetes was associated with lower rates of HbA1c testing and sub-optimal glycaemic control compared to those with usual-onset diabetes.